CO2 Emission trade in the European Union and Hungary - Szőllősi, Nikolett; Juhász, Csaba; Tamás, János (Acta Agraria Debreceniensis, 2007)
The environmental policy of the European Union focuses on decreasing emission of greenhouse gases. However there is no knowledge about the effect and the operation of the environmental economic methods which could efficiently influence this process. Therefore, practical emission trade was investigated. Recently, the commerce of AUEs started to change in Hungary, as well. Most transactions are made by a broker. Electronic commerce, which can be made with or without a broker, is spreading. The benefit of this form is that it is simple and cheap, in spite of the entrance fee of the stock exchange. This study could help to utilize carbon quotas in different types of commerce.